Meningkatkan Kemampuan Menulis Puisi Menggunakan Teknik Out Door pada Siswa Kelas VIII SMPN 8 Bandar Lampung - Ningsih, Rumdiyati (Lentera: Jurnal Ilmiah Kependidikan, 2015)
This study aims to determine the students ability to write poetry before using the technique of out door and after using the technique out door. The object of this research is class VIII SMPN 8 F Bandar lampung year 2013/2014. Data collection techniques performed through three times the test is the first test done free writing poems in class, second and third test write poetry using the technique out door individually (test 2) and in groups (test 3). The result showed that in the first test when the students write poetry in the classroom, students are less passionate and as difficult to find the words to be poetry. In the second and third tests students taken out of class, the students began to seem pleased to observe something that is in front of his eyes. Students began to write with passion. Like wise, in the third test, students seem more excited because they equate with a theme of words with a friend group. Then revealed his imagination in the form of poetry. The results of the third test is the percentage of the average value of the first test at 72.57, the average value of the second test 80 and the average value of the third test, namely 85.33 So, the difference between the first and second test is 7.43 percent, the difference between the second and third tests, namely 5.33 percent. Thus the use of techniques out door can improve the ability to write poetry in class VIII SMP Negeri 8 F Bandarlampung.